(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The Target costing is an important modern techniques strategic managerial accounting.which is been shown active adoption to changes in contemporary business environments Inaddition,they had been adopted by the units as aresult of the growth in the strategic approach in the man agement..the goal of using target costing is to build and strengthen competitive abilities of economic units thvough introducing appropriate ways to decrease cost and improving quality of product The hypothesis reflects interest in achieving the goal of the research,ie.research question,The hypothesis use target costing to assist economic units to decrease cost and in the manner that leads to competitive advantages while surviving and flourishing in current businesses, AL-Amael in dustry company represents the sample of this study.to achieve the study aims it had been divided in to three chapters the firsl chapter show the study methodology and target costing theoretical approach other chapter reach practical and conclusions also the suggested recommendation